The stabilising effect of oxides in foamed aluminium alloy scrap - Vinod Kumar, G.S.; García-Moreno, Francisco; Banhart, John; Kennedy, Andrew R. (Carl Hanser Verlag, 2015)
The expansion and stability of foams made from remelted aluminium alloy scrap has been studied. Foams made from scrap alloy contain oxide bi-films introduced from the swarf (machining chips and turnings) of LM26 alloy and these oxides act as stabilizing agents. The wettability of the oxides and hence the stabilisation is studied by varying the addition of Mg (0 to 2 wt.%) in the alloy. The viscosity of the melts with and without Mg addition is measured and correlated with foam expansion and stability. A detailed microstructural analysis of the base alloy and foam cell wall was conducted to obtain an understanding of the stabilisation behaviour of oxides.